Ungbarnabólusetning á Íslandi gegn Haemophilus influenzae af hjúpgerð b : árangur eftir sex ára notkun PRP-D (ProHIBiT) - Kristín E. Jónsdóttir; Halldór J. Hansen; Víkingur H. Arnórsson; Þröstur Laxdal; Magnús L. Stefánsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2009)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open Haemophilus influenzae type b (Hib) causes meningitis bacteremia and epiglottitis, dangerous infections, which occur mainly in children under five years of age. Incidence of Hib meningitis in that age group in Iceland was 43/100.000 1974-1988. In the fall of 1988 Icelandic health authorities decided to offer infant immunisation against Hib with PRP-D (ProHIBiT®) vaccine, product of Connaught Ltd, Canada. Results are presented of this immunisation programme which has been running since spring 1989. The vaccine is administered at the age of three, four, six and 14 months. During the first year of the immunisation programme one dose was offered to children aged 15 months up to end of third year. During the 10 years 1980-1989, 92 children had Hib meningitis, 61 Hib bacteremia or arthritis and 21 acute epiglottitis. During the five years 1990-1994 no child had Hib meningitis or epiglottitis but three had Hib bacteremia. Hib strains were 10-16% of Haemophilus influenzae strains isolated from surface swabs from 0-5 years old children at different periods until spring 1991 but became very scarse after that. Anti-PRP antibodies in blood measured <0.15 u.g/ ml in 20% of children after three doses of vaccine but >1.0j.ig/ml in 95% after four doses. No fully immunized child has had invasive Hib disease, but one had meningitis and two bacteremia after one dose of vaccine and one bacteremia after three doses. In 1993 21 fully immunized three to four years old children received a booster dose of PRP-D. Geometric Mean Titer of anti-PRP was 1.11 jig/ml before and 137.11u.g/ml after the dose. Mean antibodies against diphtheria were 0.37 IU before and 11.69 IU after the dose. It remains uncertain how long anti-PRP will last in vaccinees when Hib strains disappear. Haemophilus influenzae af hjúpgerð b (Hib) getur valdið hættulegum sýkingum í heilahimnum, blóði og barkaloki. Eru þær algengastar hjá börnum innan fimm ára aldurs ...